Expression of extracellular matrix components in the meibomian gland - Chen, Di; Chen, Xiaomin; Xie, Hua-Tao; Hatton, Mark P.; Liu, Xiaowei; Liu, Yang (Frontiers in Medicine, 2022)
Purpose: Extracellular matrix (ECM) is a key component of the stem cell local microenvironment. Our study aims to explore the periglandular distribution of major components of ECM in the Meibomian gland (MG). Methods: Human eyelids and mouse eyelids were collected and processed for immunofluorescence staining. Results: Human MG tissues stained positive for collagen IV α1, collagen IV α2, collagen IV α5, and collagen IV α6 around the acini and duct, but negative for collagen IV α3 and collagen IV α4. The mouse MG were stained positive for the same collagen IV subunits as early as postnatal day 15. Laminin α2, laminin β1 and perlecan stained the regions surrounding the acini and the acinar/ductal junction in the human MG, but not the region around the duct. Tenascin-C was found specifically located at the junctions between the acini and the central ducts. Neither agrin nor endostatin was found in the human MG tissues. Conclusion: The ECM expresses specific components in different regions around the MG, which may play a role in MG stem cell regulation, renewal, and regeneration.